A Comparison of QTc Abnormalities in Cirrhotics with Non-Cirrohotic - M Mujtaba Ali, M Abdul Quddus, Arslan Shahzad, M Fareed Khan, Sheikh Taqqi Anwar, Kapeel Raja, M Mujtaba Ali, M Abdul Quddus, Arslan Shahzad, M Fareed Khan, Sheikh Taqqi Anwar, Kapeel Raja (Journal of Rawalpindi Medical College, 2020)
Objective: To compare the frequency of prolonged QTc interval in cirrhotics with non-cirrhotics having chronic liver disease. Study design: Cohort study Place and Duration of study: Department of Gastroenterology AK CMH/Sheikh Khalifa Bin Zayed Al Nahyan Hospital Rawalakot Azad Kashmir. Six months; (27-03-2019 to 26-09-2019) Materials and Methods: One hundred patients with liver cirrhosis (group I) and 100 non-cirrhotic patients ((group II) had 12 lead ECG. QT interval was calculated. And the patients were evaluated for presence of prolonged QT interval. Statistical significant determined by chi-square test (p< 0.05 was taken as significant). Results: The mean QTc duration in Group I was 0.536 + 0.012 seconds and group II was 0.431 + 0.015 seconds (p < 0.05). Prolonged QTc interval was present among 36(36%) patients in Group I and in 6 (6%) patients in Group II. (p < 0.05). Conclusion: Our study findings revealed that cirrhotic patients have more chances of developing the QTc abnormalities as compared to the patients without the presence of cirrhotic liver.